2012
DOI: 10.2105/ajph.2011.300407
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Risk Perceptions and Vaccination Intentions: A Longitudinal Study of the First Year of the H1N1 Pandemic

Abstract: Objectives Vaccination is critical to controlling disease transmission during a pandemic, yet little is known about how the public’s risk perception and willingness to be immunized evolve as pandemics progress. We sought to evaluate longitudinal trends in risk perceptions and vaccination intentions during the 2009 H1N1 pandemic. Methods We performed a longitudinal analysis of risk perception and vaccination intention from 10 waves of a survey (May 2009 to January 2010) from a national sample of U.S. adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
146
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(170 citation statements)
references
References 23 publications
19
146
0
2
Order By: Relevance
“…1 The decision to be vaccinated depends largely upon the perceived risks and benefits, 2 potentially including the perceived risk or protection provided by an individuals’ social networks. If people associate transmission risk with the infectiousness of their social networks, increasing vaccination, resulting in “herd immunity,” should reduce the expected benefits of personal vaccination because individuals perceive lower likelihood of contact with infection.…”
Section: Introductionmentioning
confidence: 99%
“…1 The decision to be vaccinated depends largely upon the perceived risks and benefits, 2 potentially including the perceived risk or protection provided by an individuals’ social networks. If people associate transmission risk with the infectiousness of their social networks, increasing vaccination, resulting in “herd immunity,” should reduce the expected benefits of personal vaccination because individuals perceive lower likelihood of contact with infection.…”
Section: Introductionmentioning
confidence: 99%
“…The H1N1 pandemic raised national awareness of the importance of influenza vaccination 8. The estimated seasonal influenza vaccination rates for this season were higher overall 9.…”
Section: Discussionmentioning
confidence: 99%
“…55,56 The survey also collected information on health-risk factors for H1N1-related complications as summarized in the government's H1N1 vaccination recommendations. 51 I used data from three of the 12 ALP influenza surveys, which were conducted between 17 and 31 August 2009 (“wave 7”), 19 November and 10 December 2009 (“wave 9”) and 17 May and 25 June 2010 (“wave 11”), respectively.…”
Section: Data Measures and Methodsmentioning
confidence: 99%
“…Previous research based on multiple ALP waves showed that mean perceived infection risks over time closely tracked the temporal pattern of H1N1 virus activity as measured by weekly CDC data on outpatient visits for influenza-like illnesses and hospitalizations. 56 …”
Section: Data Measures and Methodsmentioning
confidence: 99%